Mitochondria of the Yeasts Saccharomyces cerevisiae and Kluyveromyces lactis Contain Nuclear rDNA-Encoded Proteins - Galopier, Aurélie; Hermann-Le Denmat, Sylvie (PLOS ONE, 2011)
In eukaryotes, the nuclear ribosomal DNA (rDNA) is the source of the structural 18S, 5.8S and 25S rRNAs. In hemiascomycetous yeasts, the 25S rDNA sequence was described to lodge an antisense open reading frame (ORF) named TAR1 for Transcript Antisense to Ribosomal RNA. Here, we present the first immuno-detection and sub-cellular localization of the authentic product of this atypical yeast gene. Using specific antibodies against the predicted amino-acid sequence of the Saccharomyces cerevisiae TAR1 product, we detected the endogenous Tar1p polypeptides in S. cerevisiae (Sc) and Kluyveromyces lactis (Kl) species and found that both proteins localize to mitochondria. Protease and carbonate treatments of purified mitochondria further revealed that endogenous Sc Tar1p protein sub-localizes in the inner membrane in a Nin-Cout topology. Plasmid-versions of 5′ end or 3′ end truncated TAR1 ORF were used to demonstrate that neither the N-terminus nor the C-terminus of Sc Tar1p were required for its localization. Also, Tar1p is a presequence-less protein. Endogenous Sc Tar1p was found to be a low abundant protein, which is expressed in fermentable and non-fermentable growth conditions. Endogenous Sc TAR1 transcripts were also found low abundant and consistently 5′ flanking regions of TAR1 ORF exhibit modest promoter activity when assayed in a luciferase-reporter system. Using rapid amplification of cDNA ends (RACE) PCR, we also determined that endogenous Sc TAR1 transcripts possess heterogeneous 5′ and 3′ ends probably reflecting the complex expression of a gene embedded in actively transcribed rDNA sequence. Altogether, our results definitively ascertain that the antisense yeast gene TAR1 constitutes a functional transcription unit within the nuclear rDNA repeats.